Advances in Synthesis and Measurement of Charge Transport in DNA‐Based Derivatives. Issue 41 (8th July 2018) - Zhuravel, Roman; Stern, Avigail; Fardian‐Melamed, Natalie; Eidelshtein, Gennady; Katrivas, Liat; Rotem, Dvir; Kotlyar, Alexander B.; Porath, Danny
Abstract: Charge transport through molecular structures is interesting both scientifically and technologically. To date, DNA is the only type of polymer that transports significant currents over distances of more than a few nanometers in individual molecules. For molecular electronics, DNA derivatives are by far more promising than native DNA due to their improved charge‐transport properties. Here, the synthesis of several unique DNA derivatives along with electrical characterization and theoretical models is surveyed. The derivatives include double stranded poly(G)–poly(C) DNA molecules, four stranded G4‐DNA, metal–DNA hybrid molecular wires, and other DNA molecules that are modified either at the bases or at the backbone. The electrical characteristics of these nanostructures, studied experimentally by electrostatic force microscopy, conductive atomic force microscopy, and scanning tunneling microscopy and spectroscopy, are reviewed. Abstract : DNA is an attractive molecule for molecular electronics due to its self‐assembly capabilities that allow the formation of complex predesigned structures and circuits. DNA derivatives are promising, as their charge‐transport properties may be improved while retaining their self‐assembly ability. Various DNA derivatives along with their synthesis and electrical characterization by several methods are reviewed, followed by a discussion on possible charge‐transport mechanisms.